Letter: the addition of an immunosuppressant in patients with unsatisfactory response to vedolizumab. Issue 7 (7th March 2018) - Macaluso, F. S.; Orlando, R.; Renna, S.; Sapienza, C.; Ventimiglia, M.; Rizzuto, G.; Cottone, M.; Orlando, A.
Abstract : Linked Content This article is linked to Strik et al and Strik and D'Haens papers. To view these articles visithttps://doi.org/10.1111/apt.13994 andhttps://doi.org/10.1111/apt.14570 .